Food Habits and Its Effect on Health of Elders in Magar Community (Surkhet Journal, 2014)
The‌ prime‌ objective‌ of‌ the‌ paper‌ is‌ to‌ find‌ out‌ the‌ situation‌ of‌ food‌ habit‌ and‌ and‌ its‌ impact‌ on‌ health‌ of‌ elderly people. This study was conducted in Magar community of Lekhpharsa VDC of Surkhet district. The study was based on descriptive research design. Only elderly magar people were the population of the study. There were 220 elderly Magar people among them.50 percent elder magar were taken as a sample by using lottry method of random sampling.The structured interview schedule was used to collect the necessary data. It was found that, among the elderly aged people, aged 60 to 64 were highest in number. Majority of respondents eat dal- tarkari (56.37%) with bhat. Maximum respondents did not eat vegetables (sag) with meal. Half of the respondents (50%) take meal thrice a day, cleaning way of fruits and water processing is not so satisfactory. Most of the respondents took meat and alcoholic drinks in their main festivals. In total of 110 respondents, majority of respondents were suffered from abdominal pain and blood pressure. This study concluded that the food habit of elderly Magar people was not found satisfactory and due to poor and unhygienic health habit majority of the respondents suffered from gastro-intestinal problems.